Financial Feasibility Analysis and Development Strategy of Kalosi Arabica Ground Coffee Agribusiness in Enrekang Regency (Ebro Brand Case Study) - Angreini, Angreini; Hastuti, Diah Retno Dwi; Rahim, Abd.; Irwandi, Irwandi; Kamaruddin, Citra Ayni (Tarjih : Agribusiness Development Journal, 2025)
This study aims to analyze the financial feasibility and formulate a development strategy for the Kalosi Brand EBRO Arabica ground coffee agribusiness in Enrekang Regency. The method used is a single-case study design with a quantitative approach using financial data for the period 2021-2025. Data were obtained through observation, interviews, and documentation. The financial feasibility analysis used Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C), with a 6% discount rate based on BRI Enrekang loan interest rates in 2025. Sensitivity analysis was conducted to test robustness under adverse scenarios. The results showed an NPV of IDR 218,390,468, an IRR of 15.19%, and a Net B/C of 1.336, indicating that this business is financially feasible even under stress conditions. The SWOT analysis places the EBRO brand in quadrant I (Growth/Aggressive) with coordinates (+1.23, +0.92), recommending an SO strategy, which includes strengthening premium branding, digital market expansion, and production modernization. The findings can be used as a reference for entrepreneurs and policymakers in the development of MSME-scale coffee agribusiness.